The Date and Function of the Samaria Ostraca - Finḳelshṭayn, Yiśraʾel (Israel exploration journal, 2021)
In this article I present two observations on the Samaria ostraca. The first relates to the date of the inscriptions, a large number of which were written on sherds of bowls that date to the early Iron IIB in the eighth century BCE. Others were inscribed on sherds of storage jars, possibly the narrow elongated type (known as ‘torpedo jar’), which dates to the same period. This supports an association of the ostraca with the days of Joash and Jeroboam II, or of Jeroboam II alone. The second observation deals with the function of the ostraca. A recent algorithmic study indicates that they were written by two scribes, probably at Samaria. This, the fact that a large number of the inscriptions were written on one type of bowl, and comparative material raise the possibility that the ostraca were related to offerings to a temple